Decompression sickness in breath-hold divers: A review - Lemaitre, F.; Fahlman, A.; Gardette, B.; Kohshi, K. (Journal of Sports Sciences, 2009)
Although it has been generally assumed that the risk of decompression sickness is virtually zero during a single breath-hold dive in humans, repeated dives may result in a cumulative increase in the tissue and blood nitrogen tension. Many species of marine mammals perform extensive foraging bouts with deep and long dives interspersed by a short surface interval, and some human divers regularly perform repeated dives to 30-40 m or a single dive to more than 200 m, all of which may result in nitrogen concentrations that elicit symptoms of decompression sickness. Neurological problems have been reported in humans after single or repeated dives and recent necropsy reports in stranded marine mammals were suggestive of decompression sickness-like symptoms. Modelling attempts have suggested that marine mammals may live permanently with elevated nitrogen concentrations and may be at risk when altering their dive behaviour. In humans, non-pathogenic bubbles have been recorded and symptoms of decompression sickness have been reported after repeated dives to modest depths. The mechanisms implicated in these accidents indicate that repeated breath-hold dives with short surface intervals are factors that predispose to decompression sickness. During deep diving, the effect of pulmonary shunts and/or lung collapse may play a major role in reducing the incidence of decompression sickness in humans and marine mammals.